Razvoj varnega sedeža vozila - Malnarič, Vili (Strojniški vestnik, 2007)
Here we present a list and order of actions to be taken for the successful development and industrialization of a safe car seat. During the seat's development, its safety role in the car has to be considered. With respect to this, the procedures defining the safety characteristics of the products have to be taken into account. The development stages for a safe car seat are merged within three phases, as follows: the preparation of the starting pointsfor the development of a safe car seat, the virtual development of a safe car seat, and the validation of a virtually developed safe car seat. The introduced procedure brings together simultaneous modern engineering and team work, shortens the development time and reduces the development costs.
Keywords: avtomobilski sedeži; razvoj izdelkov; security; varnost